Desiring the past and reimagining the present: contemporary collecting in Qatar - Exell, Karen (Museum and Society, 2017)
The collecting processes in Qatar at state level is intimately linked with the construction of a new Qatari identity for global consumption and national cohesion. At an individual level, collecting can be linked with the desire to preserve the disappearing present in the face of rapid development, as well as representing local traditions of authority and erudition. The national collections created for the first Qatar National Museum institutionalize this process and re-classify the objects as representing the newly constructed ‘Qatari’ identity. The Msheireb Arts Center holds the Echo Memory collection of found objects, collected to inspire a Qatari future but representing the lives of the South Asian community otherwise excluded from the Qatari national discourse. Using these examples, this paper situates the processes of collection, curation and display within, or in opposition to, the ongoing process of Qatari national identity construction, preservation and dissemination, and presents them as a facet of Qatar’s engagement with modernity and the reimagining of itself in the contemporary global age. Key words: Qatar, collections, modernity, national identity, authorized heritage